Efficacy and Safety of Naftopidil in Patients With Neurogenic Lower Urinary Tract Dysfunction: An 8-Week, Active-Controlled, Stratified-Randomized, Double-Blind, Double-Dummy, Parallel Group, Noninferiority, Multicenter Design - Sung, Hyun Hwan; Choo, Myung-Soo; Kim, Joon Chul; Kim, Jang Hwan; Lee, Kyu-Sung (International neurourology journal, 2020)
Purpose: The aim of this study was to evaluate the efficacy and safety of naftopidil compared with tamsulosin in patients with neurogenic lower urinary tract dysfunction (LUTD).Methods: This study was conducted as an 8-week, active-controlled, stratified-randomized, double-blind, double-dummy, parallel group, noninferiority, and multicenter clinical trial. After 2 weeks of screening, eligible subjects were randomly assigned to receive naftopidil (25 mg for 1 week followed by 75 mg for 7 weeks) or tamsulosin (0.2 mg for 8 weeks). Primary endpoint was a change of International Prostatic Symptom Score (IPSS) total score after 8 weeks of treatment.Results: One hundred ninety-four subjects with neurogenic LUTD were included into this trial. There were no differences between the 2 groups in baseline characteristics, including urodynamic study results, subtype of LUTD, pretreatment and concomitant medication, and causes of neurogenic bladder. The medication compliance rate was 94.0% (naftopidil, 93.6%; tamsulosin, 94.4%). There was a statistically significant decrease of IPSS total score at 8 weeks versus baseline in both the naftopidil (-5.64±0.66) and tamsulosin (-6.53±0.65) groups (P<0.0001 each). The mean difference between both groups was 0.89 (upper limit of 95% confidential interval, 2.72), which was lower than the noninferiority limit of 3 points. A subgroup analysis of neurologic lesions and sex found no mean difference of IPSS total score in each group. There was also no difference in safety profiles, including treatment emergent adverse events.Conclusions: Naftopidil was not inferior to tamsulosin as a therapeutic drug for patients with neurogenic LUTD and had a similar safety profile.